Study on helminths infections on rats at commercial and residential areas in Kota Kinabalu, Sabah / Arney Sapaat and Hairul Hafiz Mahsol - Sapaat, Arney; Mahsol, Hairul Hafiz (2008)
A study of helminthes infection on rats was conducted at four different locations. Kota Kinabalu port and Anjung Selera representing commercial area, whereas Indah Permai and Kingfisher represents residential area. Based on number of captures from four different locations, total number of 145 rats were caught representing of eight species. The species are Rattus rattus, Rattus norvegicus, Rattus exulans, Rattus tiomanicus jalorensis, sundamy muelleri, Rattus argentiventer and Mus custaneous which is from family Muridae and also 'shrew' from family Soricidae which is Suncus murinus species. At Kota Kinabalu port, Rattus rattus have the highest cestodes infections with infection rates of 62.5%, whereas Rattus exulans got infected from cestodes with 8.3% infection rates. At Anjung Selera, it shows that Rattus tiomanicus jalorensis were highly infected with cestodes based on 66.7% of infection rates. The highest nematode infection are on Sundamy muelleri which is 58.3%. Study at Kingfisher area shows that Rattus rattus were the most cestode infected 60.6% compared to nematoda which shows only 42.9%. At Indah Permai residential area, Mus custaneous shows the highest nematode with 66.7%, which means that the infection rates for cestode are 33.3%.